Temperature and Mass Profile of Far-infrared Skeleton Nebula - Aryal, Binil (Himalayan Physics, 2011)
Flux density variation of a newly discovered isolated far-infrared interstellar nebula (R.A. = 08h27m, Dec. = +25°54' (J2000)) is studied at 100 μm and 60 μm Infrared Astronomical Survey (IRAS) maps. The nebula contains two bright condensations ("nuclei") and several prominent filaments. The dust color temperature is estimated throughout the nebular region by dividing the 100 μm map by the 60 μm map and comparing the resulting flux I(100μm)/I(60μm) values at each map location with the values given for dust grain models by Dwek (1986). It is found that the dust colour temperature of the southern nucleus is 34±4 K and the temperature of its northern counterpart 32±4 K. The eastern filamentary structures are slightly cooler (20±2 K) than the western filamentary structures (26±3 K). Hence, the locations of the maximum emission i.e. the nuclei of the nebula are warmer than their filaments. It is interestingly noticed that there are no hints of star formation in the nebula, suggesting interaction with ambient matter or the presence of unknown external radiation. Possible explanations of the results will be explained. Key words: Nebula; Temperature; IRAS The Himalayan Physics Vol.1, No.1, May, 2010 Page:1-3 Uploaded Date: 28 July, 2011